The Impact of Working Capital Components Turnover Period Towards Market Value Ratio - Aldivitto, Derrick; Rahman, Aulia Fuad (Jurnal Ilmiah Mahasiswa FEB, 2016)
Through efficient management of working capital components (cash, accounts receivable, inventory, and accounts payable), companies can increase the value of the company. The purpose of this study is to determine the impact of working capital components turnover period towards the price to book value (PBV). This study uses 42 samples from 14 companies within three periods. The variables of this study is the PBV as the dependent variable and as the independent variables are cash turnover period, accounts receivable turnover period, inventory turnover period and accounts payable turnover period. To analyze the phenomena, the multiple linear regression is used to examine the effect of independent variables on the dependent variable. The results of the study indicate that the turnover period of cash, accounts receivable and accounts payable have significant effect to PBV, while inventory turnover period does not have significant effect to PBV. Key Words: Price to book value (PBV), cash turnover period, accounts receivable turnover period, inventory turnover period, accounts payable turnover period.